Comparison between the complete Bayesian method and empirical Bayesian method for ARCH models using Brazilian financial time series - Oliveira, Sandra C. [UNESP]; Andrade, Marinho G. (Sociedade Brasileira de Pesquisa Operacional, 2012)
In this work we compared the estimates of the parameters of ARCH models using a complete Bayesian method and an empirical Bayesian method in which we adopted a non-informative prior distribution and informative prior distribution, respectively. We also considered a reparameterization of those models in order to map the space of the parameters into real space. This procedure permits choosing prior normal distributions for the transformed parameters. The posterior summaries were obtained using Monte Carlo Markov chain methods (MCMC). The methodology was evaluated by considering the Telebras series from the Brazilian financial market. The results show that the two methods are able to adjust ARCH models with different numbers of parameters. The empirical Bayesian method provided a more parsimonious model to the data and better adjustment than the complete Bayesian method.
Keywords: ARCH models; Bayesian approach; MCMC methods